2022
DOI: 10.1097/md.0000000000029686
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated keratin 15 links to the occurrence of lymphovascular invasion, stromal cervical invasion as well as unfavorable survival profile in endometrial cancer patients

Abstract: Keratin 15 (KRT15) overexpression links with tumor initiation, metastasis, and poor survival in several solid carcinomas. While its clinical relevance is scarcely reported in endometrial cancer (EC). Therefore, the current study aimed to investigate the abnormal expression of KRT15 and its correlation with clinical characteristics, survival in EC patients. Totally, 135 surgical EC patients were enrolled. KRT15 protein expression in formalin-fixed and paraffin-embedded tumor and adjuvant tissues was detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Importantly, KRT15 is related to poor survival profile in patients with esophageal, colorectal, and endometrial carcinoma according to previous research (Lin et al 2020;Rao et al 2020;Yang et al 2022). In line with these studies, the current study disclosed that KRT15 was linked to shorter DFS and OS in RCC patients, which was confirmed by the multivariate regression analysis.…”
Section: Accepted Manuscriptmentioning
confidence: 63%
See 2 more Smart Citations
“…Importantly, KRT15 is related to poor survival profile in patients with esophageal, colorectal, and endometrial carcinoma according to previous research (Lin et al 2020;Rao et al 2020;Yang et al 2022). In line with these studies, the current study disclosed that KRT15 was linked to shorter DFS and OS in RCC patients, which was confirmed by the multivariate regression analysis.…”
Section: Accepted Manuscriptmentioning
confidence: 63%
“…KRT15 is dysregulated in patients with various cancers, including urinary tract carcinomas (Tai et al 2013;Lin et al 2020;Rao et al 2020;Zhong et al 2021;Yang et al 2022). A previous study reveals that KRT15 is upregulated in a subset of invasive ureteric cancers and urinary bladder cancers (Tai et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the depth of tumor invasion into the myometrium is a crucial determinant of prognosis. Furthermore, the involvement of the lower uterine segment has been associated with poorer outcomes in endometrial cancer patients, emphasizing the importance of tumor location in prognostication [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical field, KRT15 exhibits diagnostic value and prognostic value in gastric, colorectal, endometrial, and breast invasive cancer (13,14,19,20). Regarding its application in patients with liver cancer, one previous bioinformatic study reported that KRT15 is an upregulated gene in patients with liver cancer with viral infection compared with controls (19).…”
Section: Discussionmentioning
confidence: 99%